1988
DOI: 10.1159/000124997
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Central Nervous System-Pituitary-Adrenal Axis in Rats after Neonatal Treatment with Monosodium Glutamate

Abstract: We have studied the regulation of adrenal function in male rats treated neonatally with monosodium glutamate (MSG) and in littermate controls. When 6–7 months old, MSG-treated rats presented reduced body, adrenal and pituitary weight, obesity, atrophy of the optic nerve and damage of the arcuate nuclei (ARN) of the hypothalamus. MSG-treated rats showed increased serum corticosterone (CORT) levels under resting conditions; after ether stress the increase in serum CORT was greater in MSG animals when compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
1
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 30 publications
7
32
1
2
Order By: Relevance
“…MSG has been demonstrated to exert neuronal toxic e ects in the central nervous system (CNS), including the hypothalamopituitary (HP) axis (3,(20)(21)(22)(23). e plasma levels of gonadotropic hormones (FSH and LH) and testosterone, and the total number of Leydig cells have been reported to be signi cantly decreased in prepubertal rats treated with 4 mg/kg body weight of MSG (9).…”
Section: Discussionmentioning
confidence: 99%
“…MSG has been demonstrated to exert neuronal toxic e ects in the central nervous system (CNS), including the hypothalamopituitary (HP) axis (3,(20)(21)(22)(23). e plasma levels of gonadotropic hormones (FSH and LH) and testosterone, and the total number of Leydig cells have been reported to be signi cantly decreased in prepubertal rats treated with 4 mg/kg body weight of MSG (9).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have also proven that alterations in the central nervous system (CNS)-pituitary-adrenal axis (including an increase in serum levels of corticosterone and ACTH) as well as in the nerve growth factor (NGF) and neuropeptide Y (NPY) concentrations in the hypothalamic and pituitary glands can be induced in MSG-treated neonatal rats [8,9]. Furthermore, several researchers have reported that systemic or dietary MSG administration caused prominent increases in the glutamate levels in adult animals, although there were some differences between glutamate levels in the plasma and cerebrospinal fluid (CSF) depending on the administration route [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…2,3,4,6,7 Also, the changes in hypothalamic neuronal function particularly enhance hypothalamo-pituitary-adrenal (HPA) axis activity. [8][9][10][11][12] It is known that hypophagic, 13 MSG-damaged rats are characterized by increased adiposity and insulin resistance; 14 however, the exact mechanisms whereby these abnormalities develop are not fully understood. These MSG-induced changes in HPA axis activity, a key function for maintaining homeostasis, have been attributed to dysfunctions of several hypothalamic peptidergic and monoaminergic systems [15][16][17] driving pituitary function, and, in turn, modifying adrenal development and function, 11 thus resulting in enhanced corticoadrenal activity.…”
Section: Introductionmentioning
confidence: 99%
“…These MSG-induced changes in HPA axis activity, a key function for maintaining homeostasis, have been attributed to dysfunctions of several hypothalamic peptidergic and monoaminergic systems [15][16][17] driving pituitary function, and, in turn, modifying adrenal development and function, 11 thus resulting in enhanced corticoadrenal activity. [8][9][10][11][12] The bi-directional crosstalk between HPA axis and adipose tissue activities is widely accepted. 18 We recently demonstrated that the peripheral satiety signal leptin, 19 a physiological inhibitor of ACTH-driven adrenal glucocorticoid production, 20 is several fold increased in the circulation of MSG rats shortly after the end of treatment, and is even more pronounced at adulthood.…”
Section: Introductionmentioning
confidence: 99%